Peran Dan Praktik Artifical Intelligence Dalam Efisien Promosi - Rezario Febrianta Chandra; Ade Nur Saleha; Ahwe Eliza Nanda; Epehulisa Br Ginting; Maria Meisien; Mutia Dwi Ananda; Nur Aini (Politeknik Raflesia Press, 2025)
Artificial Intelligence (AI) has become a crucial technology in enhancing promotional efficiency in marketing. This study aims to analyze the role and practices of AI in promotional strategies using a qualitative method with a literature review approach. This method was chosen to examine various academic sources, journals, and previous research to gain a deeper understanding of AI implementation in marketing strategies. The findings indicate that AI plays a role in automating marketing, analyzing customer behavior, and improving audience targeting accuracy. Various AI practices in promotions include the use of machine learning algorithms, AI-powered chatbots, and big data analytics, enabling businesses to provide more personalized customer experiences and increase sales conversion. Additionally, AI supports promotional efficiency through more precise market segmentation, content personalization, and predictive analysis, helping companies develop more effective marketing strategies. Despite its numerous benefits, AI implementation also faces challenges such as data privacy issues, ethical concerns, and technological infrastructure limitations in some businesses. Therefore, this study recommends more optimal AI adaptation strategies to ensure its effective utilization in enhancing promotional efficiency and business competitiveness.